Summary of Hypobaric Research in China and the West - Stanley P.Burg (Zhileng xuebao, 2007)
A hypobaric storage system controls the O2 concentration by regulating the atmospheric pressure,but its technology and effect differ from CA entirely.At a low pressure the CO2,C2H4,and volatile contaminant concentrations present in the incoming air decrease by up to 99% when the air expands during entry into the vacuum storage chamber,and increased gaseous diffusion and respiratory inhibition cause different commodity types to tolerate 0.1%-0.2% O2.Increased gaseous diffusion also promotes the escape of CO2,NH3 and C2H4 from within the commodity,while continuous air-changes flush these gases from the storage chamber.During ultra-low pressure hypobaric storage at 1.33-2.67 kPa a high relative humidity and the prevention of convective and radiant heat uptake by the commodity limit its water loss to the amount that can be evaporated in response to the small amount of respiratory heat it produces.O2 is so scarce that a horticultural commodity's respiratory heat production and ability to transfer heat by convection are inhibited by 90%,An ultra-low pressure prevents bacterial and mold growth,kills insects,prevents CO2-damage,inhibits ethylene production by >90%,inhibits toxic succinate formation,limits ascorbic acid loss,and inactivates ethylene forming enzyme.Therefore,the hypobaric equipment is the most beneficial for horticultural commodity storage.The paper will summarize hypobaric research results and the development of LP systems in the West,and evaluate important differences between hypobaric research in China and the West.